(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Sushentsev A. A. Conditions of developing competitiveness among future electricians in the educational process of a higher school. The article deals with the issue as for developing competitiveness among future electricians studying at higher schools of the first and second level of accreditation. The author gives a theoretical analysis into scholarly and pedagogical literature devoted to the study of pedagogical conditions of training competitive specialists in the educational process of a higher school.